A Canadian Multicentre Case-Control Study of Sporadic Escherichia coli 0157:H7 Infection. (1999) - Holton, Donna; Wilson, Jeff; Ellis, Andrea; Haldane, David; April, Nicole; Grimsrud, Karen; Friesen, Brent; Spika, John
Abstract : OBJECTIVE: To evaluate further risk factors for Escherichia coli 0157:H7 infection including consumer preferences related to the consumption of ground beef and the role of person-to-person transmission of this infection. PATIENTS AND METHODS: A case-control study of sporadic E coli 0157:H7 infection was undertaken in five Canadian cites from June to December 1991. One hundred cases of E coli 0157:H7 infection were age- and sex-matched to 200 neighbourhood controls. Cases and controls were interviewed face-to-face to obtain information on potential risk factors for infection and health outcomes. Daycare providers of case and control children were interviewed regarding risk factors for infection at the institutional level. Contacts of cases and controls who reported diarrhea in the seven days before the case onset date were also interviewed about their symptoms and risk factors. RESULTS: All cases had diarrhea during the course of their illness and 90 (90%) reported bloody diarrhea. Four (4%) were reported to have developed hemolytic uremic syndrome; however, there were no fatalities. Sixty-one (61%) of patients were hospitalized. Two variables were associated with infection in the final conditional logistic regression model: eating pink hamburger patties (odds ratio = 12.4, P=0.0001, population attributable fraction =40.2%) and contact with a nonhousehold member suffering from diarrhea (odds ratio = 7.0, P=0.0054, population attributable fraction = 10.3%) in the seven days before illness. Forty per cent of cases and controls who indicated that they prefer well done hamburgers said they would eat a 'pink' hamburger if served to them rather than ask that the hamburger be cooked longer. CONCLUSIONS: Health care workers should remain vigilant in their efforts to educate the public as to the risks associated with the consumption of ground beef that is inadequately cooked, and the importance of personal hygiene in the prevention of enteric illness.